2016
DOI: 10.1002/hed.24391
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell cancer of the nasal cavity: New insights and implications for diagnosis and treatment

Abstract: Local tumor control is crucial, even if it makes radical surgery necessary. Postoperative epithetic treatment enables reliable follow-up examinations. Regional metastases at the time of diagnosis are rare. Neck dissection should therefore be reserved for cases of suspected metastasis. HPV may also play a role in the etiology of SCC of the nasal cavity. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2112-E2117, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 28 publications
9
49
1
Order By: Relevance
“…So far, only few data exist regarding the impact of HPV positivity in nasal SCCs. HPV positivity was reported in 10 up to 62% of carcinomas [3, 12] and former works demonstrated that HPV positivity was a favorable prognostic factor for nasal SCCs [12, 13]. Chowdhury et al showed that median overall survival was 54 months in HPV positive compared to 12 months in HPV negative sinonasal SCCs [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, only few data exist regarding the impact of HPV positivity in nasal SCCs. HPV positivity was reported in 10 up to 62% of carcinomas [3, 12] and former works demonstrated that HPV positivity was a favorable prognostic factor for nasal SCCs [12, 13]. Chowdhury et al showed that median overall survival was 54 months in HPV positive compared to 12 months in HPV negative sinonasal SCCs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, due to unspecific and partially overlapping anatomic boundaries and definitions in nasal cavity, it is sometimes difficult to clearly allocate SCCs to distinct anatomic subsites. As already raised by Becker et al, unselected analysis of carcinomas of the nasal cavity, paranasal sinuses and nasal vestibule, without differentiation according to anatomic subsites, cause inhomogeneous results, which may lead to wrong conclusions [3]. Therefore, all patients with uncertain or incomplete data regarding tumor subsite were excluded from analysis a priori to obtain a homogenous patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At last, maxillary osteolysis can be observed in malignant tumors like mucoepidermoid carninoma, squamous-cell carcinoma and lymphoma [19, 20]. Extranodal NK/T-cell lymphoma associated with Epstein-Barr virus infection has to be highlighted because of its severity and the difficulties to diagnose it.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Squamous cell carcinoma is the most common histology, followed by adenoid cystic and adenocarcinoma. 3,4 Another distinctive feature of septal cancer is the lack of consensus regarding its classification. 3,4 Another distinctive feature of septal cancer is the lack of consensus regarding its classification.…”
Section: Introductionmentioning
confidence: 99%